2016
DOI: 10.17269/cjph.107.5084
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of gastroschisis in Canada, 2006–2011: An exploratory analysis

Abstract: OBJECTIVES: Gastroschisis is a serious birth defect of the abdominal wall that is associated with mortality and significant morbidity. Our understanding of the factors causing this defect is limited. The objective of this paper is to describe the geographic variation in incidence of gastroschisis and characterize the spatial pattern of all gastroschisis cases in Canada between 2006 and 2011. Specifically, we aimed to ascertain the differences in spatial patterns between geographic regions and identify signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
19
0
3
Order By: Relevance
“…This was observed both in the general rate reported by the CCASS ( Public Health Agency of Canada and Health Canada, 2013 ) and in the age-adjusted and age-unadjusted data reported by ( Bassil et al, 2016 ). This result is consistent both with the uniform findings of all seven studies which have examined this question ( Torfs et al, 1994 ; Werler et al, 2003 ; Forrester and Merz, 2007 ; Draper et al, 2008 ; van Gelder et al, 2009a ; David et al, 2014 ; Skarsgard et al, 2015 ) including several prior reports from the Canadian Surgical Surveillance Group on this subject ( Alshehri et al, 2013 ; Butler et al, 2015 ; Skarsgard et al, 2015 ; Bassil et al, 2016 ; Puligandla et al, 2017 ) presumably reporting on cases which overlap in part with some of the subjects reported herein by CCASS ( Moore et al, 2013 ). This uniformity of the literature in this subject is indeed noteworthy.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…This was observed both in the general rate reported by the CCASS ( Public Health Agency of Canada and Health Canada, 2013 ) and in the age-adjusted and age-unadjusted data reported by ( Bassil et al, 2016 ). This result is consistent both with the uniform findings of all seven studies which have examined this question ( Torfs et al, 1994 ; Werler et al, 2003 ; Forrester and Merz, 2007 ; Draper et al, 2008 ; van Gelder et al, 2009a ; David et al, 2014 ; Skarsgard et al, 2015 ) including several prior reports from the Canadian Surgical Surveillance Group on this subject ( Alshehri et al, 2013 ; Butler et al, 2015 ; Skarsgard et al, 2015 ; Bassil et al, 2016 ; Puligandla et al, 2017 ) presumably reporting on cases which overlap in part with some of the subjects reported herein by CCASS ( Moore et al, 2013 ). This uniformity of the literature in this subject is indeed noteworthy.…”
Section: Discussionsupporting
confidence: 51%
“…Figure 1 redraws the pediatric epidemiology data from ( Public Health Agency of Canada and Health Canada, 2013 ) and presents data on total congenital anomalies, cardiovascular defects, orofacial defects, Downs Syndrome, gastroschisis, age-unadjusted, age-adjusted gastroschisis data (from Bassil et al, 2016 ) and limb deficiency data. In most cases the incidence data obviously peaks in the northern Territories of Nunavut and / or Northwest Territory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analyses have explored the epidemiology of GS, including maternal, 17,18 sociodemographic, and environmental predictors 19 of GS occurrence. 20 In addition to validating previously established correlations between GS and young maternal age, illicit drug use, and smoking, 17,18,21,22, CAPSNet data have shown a correlation with maternal diabetes, use of medications to treat depression, 17 and low community income. 19 CAPSNet data have also demonstrated evidence of spatial clustering of GS cases within Canada, adding to speculation that environmental factors may contribute to its occurrence.…”
Section: Gastroschisismentioning
confidence: 69%
“…19 CAPSNet data have also demonstrated evidence of spatial clustering of GS cases within Canada, adding to speculation that environmental factors may contribute to its occurrence. 20 Although GS is thought of as an isolated structural anomaly, a CAPSNet study revealed a high rate of autopsy-confirmed lethal anomalies among pregnancies ending in termination, stillbirth, or death within 24 hours of birth. 23 Optimal delivery planning has been studied in several recent CAPSNet studies.…”
Section: Gastroschisismentioning
confidence: 99%